ENT530: Mydin / Mohd Shamirul Mohd Shafridin … [et al.] - Mohd Shafridin, Mohd Shamirul; Mohd Rosli, Aimie Diyanna; Ghazali, Intan Izzati; Khair Siddik, Nur Afiqah Nadhirah (2018)
Mydin Mohamed Holdings Berhad have been recognized by all customers and it is the largest hypermarket chain in Malaysia. Mydin Mohamed Holdings Berhad (HQ) was established in 1940 and based in Subang Jaya, Malaysia. The founder was Gulam Husen Jamal an immigrant from India, a father to Mydin Mohamed. Before starting this business, his father Gulam Husen Jamal was operated Mydin business in 1918 at Penang. Since the shop had been destroyed during the World War II, Mydin Mohamed was continuing the trades of wholesaling in 1957 at Kelantan. In 2011, MYDIN, along with other major hypermarkets such as Tesco and Carrefour participated in the TUKAR programme under the Economic Transformation Programme. The programme is aimed to transform 100 selected sundry shops into modern mini marts. The company is responsible for training the shops and providing assistance after transforming as mini marts along with Tesco. In July 2013, MYDIN's then ventured into the high-end retailing with the opening of the first SAM's Groceria outlet at the Gurney Paragon in Penang in July 2013. SAM affectionately stands for Saya Anak Malaysia (I am Malaysian). Nowadays, Mydin business activity is in retailing and wholesaling. The product range divide into food line, household, soft-lines and hard-linesitems. Hard-line products include hardware, electrical, stationery, porcelain and toys. And the soft-line comprises of textiles and fabrics products. The number of outlets encompasses 23 malls, 24 hypermarkets where each is located in the malls, 16 emporiums, 3 bazaars, 47 minimarkets (MyMydin), 12 convenience shops (MyMart), 4 franchise outlets (Mydin Mart), 7 SAM'S Groceries supermarkets, 1 stand-alone SAM'S Deli restaurants and 179 KR1M branches.